THE USE OF A HYDROGELS - ACTIVE ADHESIVE POLYMER STAGES, SATURATED CHLORHEXIDINE BIHLYUKONATOM IN REMOVABLE PROSTHETICS TO ACCELERATE THE REGENERATION OF ORAL MUCOSA - N.Y. Komarytsia; O. V. Suberliak; N. B. Semeniuk; U. V. Vovk (Ukrainian Medical Stomatological Academy, 2016)
Removable laminar dentures can cause changes in the mucous membranes of the oral cavity (MMOC), which are caused by toxic, chemical, allergic, thermal factors, mechanical trauma of the mucosa and contribute to the appearance of pathogenic microflora, the development of inflammation of the oral mucous membrane. One of the nowadays areas of biomedical materials sciences is the search of new polymers and mineralpolymer compositions that can be used as a medical preparative depot. The article presents the results of the study of laboratory and technical combination of the hydrogel of adhesive-active polymer saturated with chlorhexidine bigluconate with the basis of removable acrylic denture and the use of the modified prosthesis in the clinic. The use of elastic lining from a hydrogel material is attractive from the point of high biotolerance, sorption ability of pharmaceutical ingredients and is characterized by highly elastic condition. For example clinical observation of the patient has shown the stages of manufacture of removable laminar denture from acrylic plastic "Ftoraks" combined with the hydrogel of adhesive-active polymer saturated with chlorhexidine bigluconate. Patient K., 54 years-old, appealed to the Dental Medical Center of Danylo Galytsky Lviv National Medical University. The patient complained of problems with chewing the food, aesthetic defect, bad breath. A clinical examination revealed the root of the 11 tooth. Artificial patient's crowns 13, 12, 21, 22, 23 with the roots of the teeth were taken out and laid in the holes of the teeth as removable, together with prosthesis with the lock fixing. After removing the root complete removable denture on the upper jaw was made according to the traditional methodology. The finished acrylic denture in the projection phase distorted mucous, mill created a niche for placement of the hydrogel of adhesive-active polymer. Functional impression obtained model from the silicone. Acrylic denture filled in the niches of the hydrogel, covered with a model made of silicone to provide a custom configuration of the inner surface of the prosthesis. Polymerization was carried out with the use of developed technical stages. Evaluation of the efficiency of hydrogel of adhesive-active polymer composition saturated with chlorhexidine bigluconate was carried out according to the results of dynamic observation of the clinical picture. It was found out, that use of elaborated construction improves epithelialization process of damaged tissues in consequence of the direct impact of pharmaceutical product on tissue prosthetic bed, provides receipts strictly controlled amount of medicine in the affected area, prevents the spread of a medicament across the oral cavity, also exacts uncontrolled effect on the mucous membrane and ingress of the preparation in the gastro-intestinal tract. Composition based on hydrogel of adhesive-active polymer prevents the penetration of oral microflora, including potentially harmful types of microorganisms in the wound area, thus performing a barrier function. Improving the efficiency of treatment is associated with a decrease in negative effect of clinical manifestations of removable prosthetics, allows reducing and amortizing the chewing pressure peaks, creating favorable conditions for further prosthetics.